How to start and run a petsitting business a step-by-step guide to setting up a successful enterprise in this rapidly expanding market - McKenzie, Fiona. (How To Books, 2008)
With accounts of the authors' and others' own experiences of setting up petsitting businesses, this book offers a step-by-step guide to starting and running a petsitting business. It includes information and advice on marketing, legal issues, pet care, advertising, insurance, licensing and other issues.